2013
DOI: 10.5507/bp.2012.012
|View full text |Cite
|
Sign up to set email alerts
|

Real time 3-dimensional transesophageal echocardiography is more specific than 2-dimensional TEE in the assessment of left atrial appendage thrombosis

Abstract: Background. In patients indicated for detection of intraatrial thrombus (T), 2-dimensional transesophageal echocardiography (2DTEE) is routinely used but differentiation between T and trabeculae or artifacts in the left atrial appendage (LAA) is often difficult. Aims. To compare the diagnostic value of real time 3D-transesophageal echocardiography (RT3DTEE) and 2DTEE in the assessment of LAA thrombosis. Patients and Methods. One hundred and ten consecutive patients (73M, aged 64+-13) were examined by 2DTEE. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Administration of echo contrast (eg, Sonovue, Optison) to look for a filling defect can also improve diagnostic certainty, although most TOE platforms are not optimised for use with echo contrast 36. Combined 2D and 3D TOE offers advantages including improved differentiation of thrombus from myocardium and pectinate muscles,37 38 more accurate measurement of LAA size39 and superior visualisation of LAA anatomy (important in multilobed LAA) and surrounding structures 40…”
Section: Cardiac Source Of Embolismmentioning
confidence: 99%
“…Administration of echo contrast (eg, Sonovue, Optison) to look for a filling defect can also improve diagnostic certainty, although most TOE platforms are not optimised for use with echo contrast 36. Combined 2D and 3D TOE offers advantages including improved differentiation of thrombus from myocardium and pectinate muscles,37 38 more accurate measurement of LAA size39 and superior visualisation of LAA anatomy (important in multilobed LAA) and surrounding structures 40…”
Section: Cardiac Source Of Embolismmentioning
confidence: 99%
“…Recently, Marek et al demonstrated an additional value for RT3D TEE for discrimination of LAA thrombi and identification of muscular trabeculae [14]. Beside improved detection of LA thrombi, RT3DE can be helpful in the discrimination and localization of multiple masses in the LA atrium as illustrated in .…”
Section: Cardiac and Vascular Thrombi Spontaneous Echo Contrastmentioning
confidence: 99%
“…Real time three‐dimensional transesophageal echocardiography (3DTEE) has been more recently described for LAA imaging and has shown to be efficient for thrombus assessment in case reports or noncomparative studies . Only one study previously compared 2DTEE and real time 3DTEE for thrombus assessment in the LAA; unfortunately, no actual LAA thrombus was found in this series, and no validation with CT scan was performed in case of remaining doubt after TEE, rendering the results of this study difficult to interpret and to consider in daily practice. Moreover, the 3D imaging of the LAA always follows a regular 2D evaluation, and the additional value of systematic 3D imaging of the LAA remains unclear.…”
Section: Introductionmentioning
confidence: 99%